The Challenges of Environmental Protection in Outer Space Following Russia’s Anti-Satellite (ASAT) Weapon Test Activities - Claudya, Ribqha; Handayani, Irawati (Yustisia, 2024)
One of the effects of space activities is the creation of space debris that can endanger either the space environment or the Earth’s environment. In response to concerns regarding a swift escalation in space debris, Russia tested its Anti-Satellite (ASAT) Weapon by deploying the PL-19 Nudol missile against its satellite, Cosmos 1408, generating space debris. This situation certainly raises the question of how to protect the environment in space and whether international environmental law that provides a legal framework for protection in the world can also be applied in outer space. This article offers a new perspective on implementing international law to protect the space environment. This study adopts  normative  juridical  research  methods  by  utilizing  a statute and case approach to analyze the research.  The analysis showed that space debris generated from ASAT Weapon testing activities by Russia is regarded as harmful contamination under Article IX of OST under the interpretation of the term through the method of interpretation regulated in the 1969 VCLT because these activities produce long-lived space debris. Further, Russia violated the principles of environmental protection in space by failing to fulfill the obligations contained in these principles, such as taking precautionary measures and international consultations before carrying out such test activities.